Quantitative ecotoxicology - Newman, Michael C. (Boca Raton, FL : Taylor & Francis, 2012)
"This book provides a quantitative treatment of the science of ecoto xicology. The first chapters consider fundamental concepts and definiti ons essential to understanding the fate and effects of toxicants at var ious levels of ecological organization as covered in the remaining chap ters. Scientific ecotoxicology and associated topics are defined. The h istorical perspective, rationale, and characteristics are outlined for the strong inferential and quantitative approach advocated in this book . The general measurement process is discussed, and methodologies for d efining and controlling variance, which could otherwise exclude valid c onclusions regarding ecotoxicological endeavors, are considered.Ecotoxi cological concepts at increasing levels of ecological organization are discussed in the second part of the book. Quantitative methods used to measure toxicant effects are outlined in this section. The final chapte r summarizes the book with a brief discussion of ecotoxicological asses sment. Numerous figures and tables accompany text, with many statistica l tables found in the appendix for quick reference. Although the book p rimarily focuses on aquatic systems, with appropriate modification the concepts and methods can be applied to terrestrial systems"--
Includes bibliographical references and index.
Keywords: Pollution -- Environmental aspects -- Measurement; Environmental toxicology -- Mathematics